Influence of Microbial Preparations on Triticum aestivum L. Grain Quality - Lyudmila Chaikovskaya; Nina Iakusheva; Olga Ovsienko; Lyudmila Radchenko; Vladimir Pashtetskiy; Marina Baranskaya (International Journal of Plant Biology, 2022)
Gluten, protein and amino acid composition play an important role in grain quality assessment. Areas of interest of our research include essential amino acids, which are not synthesized in the human body. It is a commonly known fact that large doses of mineral fertilizers increase grain crops’ yield and quality. However, fertilization leads to undesirable effects—in particular, environmental pollution. This creates a need to replace mineral fertilizers, at least partially, with alternative methods. One such method is the use of microbial preparations in modern technologies for growing cereals. This research, therefore, aimed to study the effect of presowing seed inoculation with a microbial preparation (based on phosphate-mobilizing bacterium Lelliottia nimipressuralis CCM* 32-3) on T. aestivum grain quality, namely the content of gluten, protein and amino acids. The analysis of three-year field experiments showed that the highest values were obtained when using the microbial preparation against the background of mineral fertilizers at the rate of P30. Presowing seed inoculation contributed to a significant increase in grain productivity (by 31.5% compared to control). The content of protein and gluten in the grain also increased up to 12.5 % and 28.0%, while in the control, these figures were 10.8% and 21.2%, respectively. Moreover, the total content of amino acids in wheat grain in the variant inoculation + fertilizers (P30) was the highest compared to those without inoculation. The following excess was noted: by 52% compared to control (without fertilizers); and by 29%, 17% and 10% in variants with mineral fertilizers at the rate of P30, P60, and P90, respectively. The obtained research results indicate that the combined application of mineral fertilizer Ammophos (at the rate of P30) and microbial preparation based on the phosphate-mobilizing bacterium L. nimipressuralis CCM 32-3 for presowing seed inoculation is an effective technique that improves the yield and quality indicators of winter wheat grain under the conditions of southern regions with insufficient moisture supply.